Clinical Retrospective Cohort Study on the Effectiveness of Chitosan Zinc Oxide Cream for Accelerating Healing in Diabetic Ulcer Patients - Dahrizal, Dahrizal; idramsyah, Idramsyah; Septiyanti, Septiyanti (Poltekita: Jurnal Ilmu Kesehatan, 2025)
The evolution of wound dressings has shifted from simply covering wounds to maintaining a moist environment. Chitosan, derived from chitin, and Zinc Oxide (ZnO) are well-known for their roles in wound healing. Chitosan is used due to its natural polymer properties, and ZnO is used to promote cell growth. This study investigates the effectiveness of chitosan zinc oxide cream as a primary dressing to enhance wound healing in diabetic ulcers. This quantitative research method uses a clinical retrospective cohort design. The sample used 235 verified medical records from 2018 to 2023, namely medical records of patients with stage III-IV diabetic wounds who received a primary dressing of chitosan zinc cream every 2-3 days and there was also documentation of the results of the bates-Jensen wound assessment at the first visit and a minimum of four weeks of treatment. The analysis included univariate and bivariate analyses to correlate treatment with healing progress. The results showed significant improvement (p<0.001) in wound condition after treatment with chitosan zinc oxide cream, including a reduction in wound size and depth, faster removal of necrotic tissue, and increased granulation and formation of epithelial tissue. These findings highlight the efficacy of the cream in treating diabetic ulcers, although further research is needed for other types of cancerous wounds, pressure ulcers, and chronic wounds.